Penerapan model pembelajaran tipe problem based learning untuk meningkatkan pemahaman konsep matematika SMA Al-Hassan - Nurhidayah, Nurhidayah; Waskitoningtyas, Rahayu Sri (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2023)
The purpose of this study was to find out the application of the Problem Based Learning learning model in increasing students' understanding of mathematical concepts in learning Mathematics on the material of a two-variable linear equation system in class X IPA SMA AL-HASSAN BALIKPAPAN. The implementation of this research was through a cyclical review process consisting of four stages, namely planning, action, observation, and reflection. Procedure This research was carried out in two cycles, namely the first cycle and the second cycle. Each cycle consists of 4 meetings. In this study, the subjects in this study were students of class X with a total of 20 students consisting of 9 male students and 11 female students. Data collection in this study was carried out by tests, documentation and observation. Data analysis was carried out by classifying student data, presenting data, interpreting data, and concluding. Based on the results of the study, several conclusions can be drawn to answer the question that the PBL learning model can improve students' mathematical concept comprehension tests in Class X IPA SMA AL-Hassan Balikpapan. This is based on the results of the test for understanding the mathematical concept of the two-variable system of equations (SPLDV) material for students in cycle I who achieved scores above 65 in PBM only achieving a score of 90%, the results obtained from tests of students' understanding of mathematical concepts in PBM increased from the first cycle with a score above 65 reaches 100%.